Harvesting Impact: Navigating Growth and Scaling of Digital Platforms in Mission-Driven Firms - Betsén, Petter; Gerber, Philip (My University, 2024)
This master’s thesis examines the growth and scaling of digital platforms for missiondriven firms. This has been achieved by examining two cases operating within the Swedish agri-food industry: Mylla and Skira. Twelve interviews were conducted with individuals currently or previously employed at Mylla or Skira. The findings suggest that being a mission-driven firm affects how strategic decisions are made and influences growth and scaling across three platform development stages. Firstly, during the initial growth phase, the study implies that embedding mission values early on integrates core values and the mission into every aspect of the platform from the onset, attracting producers at an early stage. Second, in the growth stage, the study finds that protecting mission values is vital to continue delivering a value proposition anchored through alignment with the mission. Lastly, during the scaling phase, the study finds that assuring mission values seems to be crucial in order to ensure that scaling efforts enhance rather than dilute the mission’s influence. The theoretical contributions of this study point towards the idea that mission-driven firms need to adopt a more cautious approach than profit-driven firms during their growth efforts, both to ensure mission alignment and due to often limited financial resources. This is aligned with the practical contribution provided that mission-driven firms ensure and leverage alignment to the mission continuously throughout the growth and scaling efforts.
Keywords: digital platform; mission-driven; agri-food industry; growth; scaling; mission impact